Distinct X chromosomal rearrangements in four haemophilia B patients with entire F9 deletion. (21st December 2015) - Nakamura, Y.; Ando, Y.; Takagi, Y.; Murata, M.; Kozuka, T.; Nakata, Y.; Hasebe, R.; Takagi, A.; Matsushita, T.; Shima, M.; Kojima, T.
Abstract : Introduction: Haemophilia B is an X‐linked bleeding disorder caused by a coagulation factor IX gene ( F9 ) abnormality. Numerous F9 defects have been identified to date; however, only a few with an entire F9 deletion have been reported in detail. Aim: To elucidate the cause of severe haemophilia B, we investigated the precise X chromosome abnormalities in four Japanese patients who did not show all amplifications in F9 ‐specific PCR. Methods: We analysed the patient's genomic DNA using Multiplex ligation‐dependent probe amplification (MLPA). To assess the extent of any deletions, we further performed mapping PCRs, inverse PCRs or long‐range PCRs and direct sequencing analyses of the X chromosome. Results: We detected entire F9 deletions in four haemophilia B patients and identified the precise deleted regions of the X chromosome including F9 . Patient 1 had a 149‐kb deletion with breakpoints 90‐kb upstream and 30‐kb downstream from F9 . Patients 2 and 3 showed 273‐kb and 1.19‐Mb deletions respectively. Patient 4 had two deleted regions: a 1663‐bp deletion 1.34‐Mb upstream from F9 and a 7.2‐Mb deletion including F9 . These distinct breakpoints found in four different patients suggest that the mechanism of X chromosome deletion may be different between individuals. Non‐allelic homologous recombination (NAHR), microhomology‐mediated break‐induced replication (MMBIR) or fork stalling and template switching (FoSTeS) may occur in respective X chromosomes of the four haemophilia B patients analysed. Conclusions: We identified diverse X chromosomal rearrangements in four haemophilia B patients, which might be caused by distinct mechanisms of genomic rearrangement.